2004
DOI: 10.1161/01.atv.0000109955.80818.8a
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Carotid Intima-Media Thickness and Plasma Antioxidants: The Los Angeles Atherosclerosis Study

Abstract: Objective-Recent epidemiologic and animal model data suggest that oxygenated carotenoids are protective against early atherosclerosis. We assessed the association between atherosclerotic progression, measured by carotid intima-media thickness (IMT), and plasma levels of oxygenated and hydrocarbon carotenoids, tocopherols, retinol, and ascorbic acid. Methods and Results-Participants were from an occupational cohort of 573 middle-aged women and men who were free of symptomatic cardiovascular disease at baseline.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 53 publications
(49 reference statements)
4
83
1
1
Order By: Relevance
“…Despite the epidemiological observation that intake of fruits and vegetables rich in carotenoids and plasma concentrations of b-carotene are both inversely related to the prevalence of type II diabetes (Coyne et al, 2005) and to the risk of future cardio-and cerebrovascular events (D'Odorico et al, 2000;Hak et al, 2003Hak et al, , 2004Dwyer et al, 254 (149) 269 (163) 273 (109) 310 (148) 0.033 Vegetables-pulses (g/day)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the epidemiological observation that intake of fruits and vegetables rich in carotenoids and plasma concentrations of b-carotene are both inversely related to the prevalence of type II diabetes (Coyne et al, 2005) and to the risk of future cardio-and cerebrovascular events (D'Odorico et al, 2000;Hak et al, 2003Hak et al, , 2004Dwyer et al, 254 (149) 269 (163) 273 (109) 310 (148) 0.033 Vegetables-pulses (g/day)…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern has been observed for cardiovascular disease (CVD) risk and death for all causes. With few exceptions, cohort studies show a higher incidence of atherosclerosis and CVD among subjects with low concentrations of plasma b-carotene and, to a lesser extent, with low dietary (or supplemental) intake of carotenoids (Kritchevsky et al, 1995;D'Odorico et al, 2000;Hak et al, 2003Hak et al, , 2004Dwyer et al, 2004), but supplementation studies with b-carotene, either alone or in combination with other antioxidants, have demonstrated no effect in primary or secondary CVD prevention (Tornwall et al, 1999;Asplund, 2002;Vivekananthan et al, 2003). Finally, low-plasma b-carotene is associated with higher mortality for all causes, but b-carotene supplementation does not reduce the risk of death significantly (Greenberg et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that people who consumed avocado regularly tended to have a sufficient nutrient supply of dietary fibre, vitamin K, vitamin E, potassium, magnesium, as well as vitamin B complex [14]. These nutrients provide a wide range of potential health benefits such as preventing hypercholesterolemia [15], vascular damage [16], and reduce the risk of atherosclerosis [17]. The consumption of avocado has been investigated to have positive effects on lipid profiles [18] by increasing HDL cholesterol levels, reducing lipid serum peroxidation, and promoting cardiovascular health [19].…”
Section: Introductionmentioning
confidence: 99%
“…Plant-based fat sources have great potentials to be used as a replacement for dairy-based fat sources in the ice cream formulation. Furthermore, plant-based sources are generally less expensive compared to dairy fat [21] and provide advantages towards health [15], [16], [17], [18], [19]. The objective of this study was to analyze the physicochemical, rheological and sensorial properties of ice cream that have been substituted with different concentrations of avocado paste.…”
Section: Introductionmentioning
confidence: 99%
“…The potent preventive effect of the Chlorella lipid fraction may have been caused by synergistic action due to the high content of multiple antioxidants, carotenoids and others. Recently, Iribarren et al (30), and Dwyer et al (31,32) have presented papers in which epidemiological study and mouse model findings support the hypothesis that increased dietary intake of lutein suppresses the progression of intima-media thickness of the common carotid arteries, and is protective against the development of early atherosclerosis. Extensive epidemiological studies also have shown that increased intake of carotenoids, especially lutein, is correlated significantly with decreased risk of cerebral stroke and coronary heart disease (33)(34)(35).…”
Section: Lipid Fractionmentioning
confidence: 95%